Slow Inactivation in Voltage Gated Potassium Channels Is Insensitive to the Binding of Pore Occluding Peptide Toxins - Oliva, Carolina (Biophysical Society, 2005)
Voltage gated potassium channels open and inactivate in response to changes of the voltage across the membrane. After removal of the fast N-type inactivation, voltage gated Shaker K-channels (Shaker-IR) are still able to inactivate through a poorly understood closure of the ion conduction pore. This, usually slower, inactivation shares with binding of pore occluding peptide toxin two important features: i), both are sensitive to the occupancy of the pore by permeant ions or tetraethylammonium, and ii), both are critically affected by point mutations in the external vestibule. Thus, mutual interference between these two processes is expected. To explore the extent of the conformational change involved in Shaker slow inactivation, we estimated the energetic impact of such interference. We used κ−conotoxin-PVIIA (κ−PVIIA) and charybdotoxin (CTX) peptides that occlude the pore of Shaker K-channels with a simple 1:1 stoichiometry and with kinetics 100-fold faster than that of slow inactivation. Because inactivation appears functionally different between outside-out patches and whole oocytes, we also compared the toxin effect on inactivation with these two techniques. Surprisingly, the rate of macroscopic inactivation and the rate of recovery, regardless of the technique used, were toxin insensitive. We also found that the fraction of inactivated channels at equilibrium remained unchanged at saturating κ−PVIIA. This lack of interference with toxin suggests that during slow inactivation the toxin receptor site remains unaffected, placing a strong geometry-conservative constraint on the possible structural configurations of a slow inactivated K-channel. Such a constraint could be fulfilled by a concerted rotation of the external vestibule.